Pengaruh Inventory Intensity, Kompensasi Eksekutif, dan Pertumbuhan Penjualan, terhadap Penghindaran Pajak - Titin Sutinah; Dinari Ambarita (Jurnal Mutiara Ilmu Akuntansi, 2026)
This study aims to examine the influence of inventory intensity, executive compensation, and sales growth on tax avoidance in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX). This type of research is quantitative research using secondary data during the period 2020–2024. The sampling method used was purposive sampling, and the sample obtained consisted of 7 companies with 35 observation data points. Data processing was carried out using the E-Views 12 statistical program. Based on the results of this study, inventory intensity, executive compensation, and sales growth simultaneously affect tax avoidance. Partially, only executive compensation has an effect on tax avoidance, while inventory intensity and sales growth have no effect on tax avoidance. This study contributes to the development of accounting and taxation literature, particularly regarding the factors influencing corporate tax avoidance practices in the non-cyclical consumer sector. The findings indicate that executive compensation plays an important role in influencing managerial decisions related to tax avoidance, whereas inventory intensity and sales growth do not significantly determine tax avoidance practices individually. Therefore, companies are expected to improve governance and transparency in executive compensation policies to minimize opportunistic actions related to tax management. In addition, future researchers are encouraged to expand the research variables and increase the number of samples in order to obtain more comprehensive results regarding the determinants of tax avoidance.